6+w=12

Simple and best practice solution for 6+w=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+w=12 equation:


Simplifying
6 + w = 12

Solving
6 + w = 12

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + w = 12 + -6

Combine like terms: 6 + -6 = 0
0 + w = 12 + -6
w = 12 + -6

Combine like terms: 12 + -6 = 6
w = 6

Simplifying
w = 6

See similar equations:

| 2(5x-31*x)= | | 9e-2=5e+26 | | 22x+26=48 | | y=0(8)+8 | | 120=(x+1)(x+20) | | 10/5x^2-20x-60=0 | | 3/4*6=c | | 2(5x-31)(2x)= | | -7(x+1)=43 | | -27+s=42 | | p+1/4/3=4/5/8 | | 26-2x=16 | | 6x^2+(-10x)+6+4x+(-5)= | | 22-2=4 | | -5x+6(3x-6)=-15-8x | | 7(2x+5)-7=32 | | 2x+(-6x)+(-5x)= | | 7/11x+(-17)=4 | | J/7=10-9j | | 11x+7=51 | | 12=(3m-17) | | (-6x)+(-x)= | | (-3x)+(-4x)+3x= | | 3=278y | | 1/3+2/3 | | -3/4m=-9/16 | | P+11/3=45/8 | | 3x/5-x/3=4 | | 7x+(-6x)= | | -3(4x+3)+4(6x+1)=43solve | | 15x^2-2x^4+27=0 | | (-4x)+6x= |

Equations solver categories